Increased risk of impulse control symptoms in Parkinson's disease with REM sleep behaviour disorder. Issue 2 (8th July 2014) - Fantini, M L; Macedo, L; Zibetti, M; Sarchioto, M; Vidal, T; Pereira, B; Marques, A; Debilly, B; Derost, P; Ulla, M; Vitello, N; Cicolin, A; et al.
Abstract : Objective: To assess the frequency of symptoms of impulse control disorders (ICD, namely pathological gambling, compulsive sexual behaviour, compulsive eating and compulsive shopping) and related behaviours (hobbyism, punding, walkabout and dopamine dysregulation syndrome) in patients with Parkinson's disease (PD) with and without probable rapid eye movement, sleep behaviour disorder (pRBD). Methods: Two hundred and sixteen consecutive PD patients, attending two university-based movement disorders clinics, were screened for p-RBD using the RBD Single Question and the RBD Screening Questionnaire (RBDSQ). Current ICDs and related behaviours symptoms were assessed with the Questionnaire for Impulsive-Compulsive Disorders in PD (QUIP)-short form. Results: PD-pRBD patients (n=106/216;49%) had a longer PD duration, a higher Hoehn & Yahr score, a greater levodopa-equivalent daily dose (LEDD), but no difference in dopamine agonist use, compared to PD-without pRBD. A higher proportion of one or more current ICDs and related behaviours symptoms was reported in PD-pRBD compared to PD-without RBD (53% vs28%; p=0.0002). In a multivariate regression analysis accounting for gender, age of onset, PD duration, PD severity, depression score and total and dopaminergic agonist-LEDD, RBD was associated to a relative risk of 1.84 for any ICD or related behaviours symptoms (p=0.01), and to a risk of 2.59 for any ICD symptoms only (p=0.001). Furthermore, PD-pRBD had a more than fourfold risk for symptoms of pathological gambling (relative risk (RR): 4.87; p=0.049) compared to PD-without pRBD. Conclusions: The present study indicates that RBD is associated with an increased risk of developing symptoms of ICDs in PD. Identifying RBD in PD may help clinicians to choose the best therapeutic strategy. Trial registration: AU1023 Institutional Ethics Committee.